2004
DOI: 10.1007/s00216-004-2779-7
|View full text |Cite
|
Sign up to set email alerts
|

Technology of production of red figure pottery from Attic and southern Italian workshops

Abstract: Samples from Greek figure vases were investigated by scanning electron microscopy coupled with energy dispersive X-ray analysis, X-ray diffraction, thermomechanical analysis and reflectance spectroscopy to achieve a technological characterisation. The vases, dating from the end of the sixth to the fourth century BC, had been excavated at Locri Epizephiri (Calabria, Italy) and attributed to Attic or local workshops, respectively. Information on the morphology of black slip areas and firing temperatures was comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…Phyllosilicates disappear at temperatures between 900 and 950°C (De Benedetto et al 2002;Damjanović et al 2011) and potassium feldspars should not be found in bodies fired above 900°C (Mirti et al 2004), indicating higher firing temperatures for samples NB-2, NB-6, Hematite, which is identified in all of the samples, is produced during pottery firing when the process is carried out in oxidizing conditions. This finding is in agreement with the reddish colour of the investigated pottery and the high iron content as determined by chemical analysis.…”
Section: X-ray Powder Diffraction (Xrpd) Analysismentioning
confidence: 94%
“…Phyllosilicates disappear at temperatures between 900 and 950°C (De Benedetto et al 2002;Damjanović et al 2011) and potassium feldspars should not be found in bodies fired above 900°C (Mirti et al 2004), indicating higher firing temperatures for samples NB-2, NB-6, Hematite, which is identified in all of the samples, is produced during pottery firing when the process is carried out in oxidizing conditions. This finding is in agreement with the reddish colour of the investigated pottery and the high iron content as determined by chemical analysis.…”
Section: X-ray Powder Diffraction (Xrpd) Analysismentioning
confidence: 94%
“…There is as yet a lack of data about red figured vase production from Magna Grecia (Canosa et al, 1996;Grave et al, 1997;Mirti, 2000;Mirti et al, 1996Mirti et al, , 2004Mirti et al, , 2006; only approximately ten fragments of Apulian red figured pottery have been analysed (Canosa et al, 1996;Grave et al, 1997), a small number and from different sites, so the results cannot be considered representative of such complex, structured and assorted production.…”
Section: Introductionmentioning
confidence: 93%
“…Archaeometric investigations on red figured pottery have so far mainly dealt with Attic production, and were aimed at understanding the specific characteristics of each step in the overall production cycle, with particular attention devoted to the technique utilized to realize the black gloss (Canosa et al, 1996;Ingo et al, 2000;Jones, 1986;Kingery, 1991;Maniatis et al, 1993;Mirti, 2000;Mirti et al, 1996Mirti et al, , 2004Mirti et al, , 2006Noble, 1960;Tang et al, 2001;Tite et al, 1982). There is as yet a lack of data about red figured vase production from Magna Grecia (Canosa et al, 1996;Grave et al, 1997;Mirti, 2000;Mirti et al, 1996Mirti et al, , 2004Mirti et al, , 2006; only approximately ten fragments of Apulian red figured pottery have been analysed (Canosa et al, 1996;Grave et al, 1997), a small number and from different sites, so the results cannot be considered representative of such complex, structured and assorted production.…”
Section: Introductionmentioning
confidence: 99%
“…As regards the Mediterranean area, abundant investigations have been reported on some well-known examples of painting on archaeological pottery such as black (and also red) gloss especially on Attic but also southern-Italian, Etruscan and Roman ceramics [1][2][3][4][5][6][7][8][9], while for other forms of decoration a site-by-site investigation is still needed. Numerous studies on the subject have been devoted in the past to the Greek civilization, as reviewed by Jones [10], while for a lot of fundamental work we are indebted to Noll [11,12].…”
Section: Introductionmentioning
confidence: 99%